Investigative studies of tracheobronchial stent design - Lin, Sin Ching (2008)
The underlying purpose of this research is therefore to: (a) propose a process methodology to fabricate custom-fit stents made from polyurethane material; (b) to suggest ways to improve the general performance of the currently available commercial stent; and (c) study the effect of stenoses on respiratory parameters such as tidal volume, flow rate, proximal pressure and lung pressure.